Validity of the Korean Version of DIVA-5: A Semi-Structured Diagnostic Interview for Adult ADHD - Hong M (Dove Medical Press, 2020)
Minha Hong,1 JJ Sandra Kooij,2,3 Bongseog Kim,4 Yoo-Sook Joung,5 Hanik K Yoo,6 Eui-Jung Kim,7 Soyoung Irene Lee,8 Soo-Young Bhang,9 Seung Yup Lee,10 Doug Hyun Han,11 Young Sik Lee,11 Geon Ho Bahn10 1Department of Psychiatry, Myongji Hospital, Hanyang University College of Medicine, Goyang, Korea; 2PsyQ, Psycho-Medical Programs, Expertise Center Adult ADHD, The Hague, The Netherlands; 3Department of Psychiatry, Amsterdam University Medical Center, Amsterdam, The Netherlands; 4Department of Psychiatry, Inje University College of Medicine, Seoul, Korea; 5Department of Psychiatry, Samsung Medical Center, Sungkyunkwan University School of Medicine, Seoul, Korea; 6Department of Clinical Psychiatry, Seoul Brain Research Institute, Seoul, Korea; 7Department of Psychiatry, College of Medicine, Ewha Womans University, Seoul, Korea; 8Department of Psychiatry, Soonchunhyang University College of Medicine, Bucheon, Korea; 9Department of Psychiatry, Nowon Eulji University Hospital, Eulji University School of Medicine, Seoul, Korea; 10Department of Psychiatry, Kyung Hee University School of Medicine, Seoul, Korea; 11Department of Psychiatry, Chung-Ang University College of Medicine, Seoul, KoreaCorrespondence: Geon Ho Bahn Department of PsychiatryKyung Hee University School of Medicine, 23 Kyungheedae-Ro, Dongdaemungu, Seoul 02447, KoreaTel +82-2-958-8556Fax +82-2-957-1997Email mompeian@khu.ac.krBackground: This study was to assess the validity of the Korean version of the semi-structured Diagnostic Interview for Adult ADHD, third edition (DIVA-5). The secondary aim was to compare sociodemographic and psychiatric comorbidities in adult patients with and without a diagnosis of ADHD.Methods: A total of 279 participants were recruited from nine psychiatric outpatient clinics in Korea. All participants were administered the Mini-International Neuropsychiatric Interview (MINI) Plus v.5.0.0, the Adult ADHD Self-Report Scale v1.1 (ASRS-v1.1) Symptom Checklist, and DIVA-5. Diagnosis concordance between two board-certified psychiatrists and DIVA-5 were analysed.Results: The DIVA-5 showed a diagnostic accuracy of 92%, a sensitivity of 91.30%, and a specificity of 93.62%. Significant clinical and demographic differences between ADHD and control groups were found.Conclusion: The Korean version of DIVA-5 is a reliable tool for assessing and diagnosing ADHD in adult Korean populations.Keywords: adult ADHD, validity, DIVA-5, Korean